GREEK «ΦΥΣΙΣ» AS THE BASIS OF GENDER STEREOTYPES - S. V. Storozhuk; I. M. Goyan (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. Considering the fact that the concept «by nature» formed the basis of diametrically different approaches to the interpretation of the place and role of women not only in Greek society, but determined the gender relations up to this time, the article examines the features of the interpretation of the term «nature» («φύσις») in Greek outlook and the impact of natural-philosophical ideas on the evolution of gender relations of Ancient period. Methodology of the study is caused by interdisciplinary approach, involving not only the use of scientific methods such as analysis, synthesis and generalization and so on. Basic principles of philosophical hermeneutics, hypothetical-deductive method and contextual analysis are used at the same time. Originality lies in the denial of existing idea in contemporary intellectual discourse that the concept «by nature» is a conceptual prerequisite for ensuring gender inequality. Against this background, it is shown that gender equality and inequalities are both caused by the dominant in the public worldview meta-narrative paradigm and specific features of interpretation of the concept «by nature» (or «nature»). So when nature is seen in physiological or empirical sense, it establishes a pattern of gender inequality. The same can occur in cases of dogmatization and mythologizing of empiricism, which appears on the ideological level as a meta-narrative. However, when the concept of «nature» acquires metaphysical meaning and is viewed as a kind of potentiality that is actualized in the presence of favorable conditions prerequisites of gender equality are emerging. Conclusions. Having considered the proposed by Greek philosophy approaches to gender interaction as a kind of stereotypes, we conclude that the development of gender relations in individual historical terms was caused by the specificity of the dominant narrative of life and world order.